Stress utilisation of jacket structure under environmental loading - Jusoh, Iberahin (Faculty of Mechanical Engineering, 1997)
The level of stress utilisation within structural elements due to external and transferred loads between structural members may be estimated. This may routinely be performed at early design stages where all loading parameters and assumptions are predicted to act on the structure that results the response under normal operating condition. The paper addresses loading parameters, discuss analysis steps that have been applied to the structure and illustrate subsequent results of the stress utilisation within the structure due to the response to external and transferred load acting on the structure. Particular application includes the studies on typical shallows or medium water depth jacket structures under normal and extreme loading conditions.